Prognostic value of left atrial strain in predicting cardiovascular morbidity and mortality in the general population. (11th December 2018) - Modin, Daniel; Biering-Sørensen, Sofie Reumert; Møgelvang, Rasmus; Alhakak, Alia Saed; Jensen, Jan Skov; Biering-Sørensen, Tor
Abstract: Aims: Left atrial (LA) enlargement predicts cardiovascular risk. The prognostic value of left atrial peak reservoir strain (LA RS) by two-dimensional speckle tracking in the general population is currently unknown. This study sought to determine the prognostic value of LA RS in the general population. Methods and results: A total of 385 participants without atrial fibrillation, heart failure (HF), and ischaemic heart disease (IHD) had an echocardiogram including left ventricular and LA speckle-tracking analysis performed. LA RS was averaged from the three apical views. The endpoint was a composite of incident IHD, HF, or cardiovascular death. Median follow-up was 12.6 years (interquartile-range 11.5–12.8 years). Follow-up was 100%. Fifty-one participants (13.3%) reached the composite outcome. LA RS was a univariable predictor of outcome [hazard ratio (HR) 1.25, 95% confidence interval (95% CI) 1.09–1.43; P  = 0.002]. However, LA RS did not remain an independent predictor of outcome after adjustment for clinical parameters. The prognostic value was modified by sex ( P  = 0.011). LA RS predicted the composite outcome in women but not in men when adjusting for clinical parameters (women: HR 1.46, 95% CI 1.05–2.02; P  = 0.025) (men: HR 0.96, 95% CI 0.81–1.14; P  = 0.65). Further adjustment for echocardiographic parameters did not significantly alter the results. LA RS added incremental prognostic information in addition to SCORE and the American Heart Association/American College of Cardiology Pooled Cohort Equation in women only. Conclusion: LA RS is a univariable predictor of cardiovascular morbidity and mortality in the general population. However, the prognostic value of LA RS is modified by sex. LA RS is an independent predictor of outcome in women but not in men.